Focusing on NK cells and ADCC: A promising immunotherapy approach in targeted therapy for HER2-positive breast cancer - Li, Feifei; Liu, Sheng (Frontiers in Immunology, 2022)
Human epidermal growth factor receptor 2 (HER2)-positive breast cancer has a high metastatic potential. Monoclonal antibodies (mAbs) that target HER2, such as trastuzumab and pertuzumab, are the cornerstone of adjuvant therapy for HER2-positive breast cancer. A growing body of preclinical and clinical evidence points to the importance of innate immunity mediated by antibody-dependent cellular cytotoxicity (ADCC) in the clinical effect of mAbs on the resulting anti-tumor response. In this review, we provide an overview of the role of natural killer (NK) cells and ADCC in targeted therapy of HER2-positive breast cancer, including the biological functions of NK cells and the role of NK cells and ADCC in anti-HER2 targeted drugs. We then discuss regulatory mechanisms and recent strategies to leverage our knowledge of NK cells and ADCC as an immunotherapy approach for HER2-positive breast cancer.